Retinal Degeneration in a Rat Model of Smith-Lemli-Opitz Syndrome: Thinking Beyond Cholesterol Deficiency - Fliesler, Steven J. (2010)
Smith-Lemli-Opitz Syndrome (SLOS) is a recessive hereditary disease caused by a defect in the last step in cholesterol biosynthesis— the reduction of the Δ7 double bond of 7-dehydrocholesterol (7DHC)— resulting in the abnormal accumulation of 7DHC and diminished levels of Chol in all bodily tissues. Treatment of rats with AY9944— a drug that inhibits the same enzyme that is genetically defective in SLOS (i.e., DHCR7, 3β-hydroxysterol-Δ7-reductase)— starting in utero and continuing throughout postnatal life, provides a convenient animal model of SLOS for understanding the disease mechanism and also for testing the efficacy of therapeutic intervention strategies. Herein, the biochemical, morphological, and electrophysiological hallmarks of retinal degeneration in this animal model are reviewed. A high-cholesterol diet partially ameliorates the associated visual function deficits, but not the morphological degeneration. Recent studies using this model suggest that the disease mechanism in SLOS goes well beyond the initial cholesterol pathway defect, including global metabolic alterations, lipid and protein oxidation, and differential expression of hundreds of genes in multiple ontological gene families. These findings may have significant implications with regard to developing more optimal therapeutic interventions for managing SLOS patients.